2009
DOI: 10.1590/s1984-46702009000300009
|View full text |Cite
|
Sign up to set email alerts
|

The endemic and threatened lizard Liolaemus lutzae (Squamata: Liolaemidae): current geographic distribution and areas of occurrence with estimated population densities

Abstract: ABSTRACT. Liolaemus lutzae Mertens, 1938 is a critically endangered lizard endemic to the restinga habitat of the state of Rio de Janeiro. We surveyed 25 restinga habitats in order to locate remaining populations, evaluate the status of the species, and determine the nature of local habitat degradation. We found remnant populations of L. lutzae in 18 restinga habitats of six municipalities. The conservation status of each population varied between areas: the population of Grumari, in Rio de Janeiro municipalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…We used the occurrence records of Liolaemus lutzae from Rocha et al (2009a) (Table 1, Figure 1), excluding the population from Praia das Neves (state of Espírito Santo), due to this population resulting from an experimental introduction in the area and not within the original species distribution (see Soares and Araújo, 2008). Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used the occurrence records of Liolaemus lutzae from Rocha et al (2009a) (Table 1, Figure 1), excluding the population from Praia das Neves (state of Espírito Santo), due to this population resulting from an experimental introduction in the area and not within the original species distribution (see Soares and Araújo, 2008). Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Modified from Rocha et al (2009a To create the potential distribution model, we used the software MaxEnt 3.2.3. Despite the availability of different methods for potential distribution modelling, some studies have shown the Maximum Entropy as one of the best performing algorithms (e.g., Elith et al, 2006;Costa et al, 2010;Giovanelli et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations